Solve for: номер

Expression: $$\left. \begin{array} { l } { - \frac { 1 } { 2 } x + 1 \frac { 1 } { 2 } = \frac { 1 } { 2 } ( 3 - x ) } \end{array} \right.$$

Multiply both sides of the equation by $2$.

$$-x+1\times 2+1=1\left(3-x\right)$$

Multiply $1$ and $2$ to get $2$.

$$-x+2+1=1\left(3-x\right)$$

Add $2$ and $1$ to get $3$.

$$-x+3=1\left(3-x\right)$$

Use the distributive property to multiply $1$ by $3-x$.

$$-x+3=3-x$$

Add $x$ to both sides.

$$-x+3+x=3$$

Combine $-x$ and $x$ to get $0$.

$$3=3$$

Compare $3$ and $3$.

$$\text{true}$$

This is true for any $x$.

$$x\in \mathrm{R}$$